PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VA SD NEGERI 116 PEKANBARU - ', Nuraini; ', Hamizi; ', Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem underlying this study is the low learning results can be seen in the learning process, teachers do apperception, but not as much as possible, teachers convey meteri only with the lecture method alone causing boredom in students, less teachers guide students in doing the exercises. Noting the above conditions, the researchers apply to the type of cooperative learning model Numbered Heads Together (NHT). NHT type cooperative learning model can improve student learning outcomes Elementary School class VB 116 Pekanbaru. Subjects in this study were students Elementary School VB 116 Pekanbaru academic year 2014/2015 the number of students 38 people. This study design using Action Research (PTK) done in two cycles, each cycle is done twice a meeting with one final replay. This research aims to improve the learning outcomes of mathematics in primary school students of class VB 116 Pekanbaru with the implementation of cooperative learning model with NHT. The results showed that the application of cooperative learning model NHT can improve students' mathematics learning outcomes Elementary School class VB 116 Pekanbaru. At the beginning of the data base score 60.26 (not completed) then the first cycle increased to 68.82 (not finished) and the second cycle increased to 90.00 (complete). Increased mastery learning hail from a base score to uh I adalah14,21% and an increase of the base score to UH II become 49.35%. The activities of teachers and students at the first meeting was 46.87% and 43.75% (or less), the second meeting increased to 59.38% and 56.25% (enough), the third meeting increased to 78.13% and 75.00 % (good) and the fourth meeting increased to 96.88% and 93.75% (very good). Based on the explanation of the above it can be concluded that the application of cooperative learning model NHT can improve students' mathematics learning outcomes Elementary School class VB 116 Pekanbaru.Keywords: Cooperative Learning NHT type, Mathematics Learning Outcomes